Analysis of the Effect of Capital, Production Costs and Business Length on MSME Income in Sabangau District, Palangka Raya City - Novi Susanti (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2020)
This study aims to analyze or find out whether capital, production costs and length of business have a partial effect on the income of MSMEs in Sabangau District, Palangka Raya City. to analyze or find out whether capital, production costs and length of business simultaneously affect the income of MSMEs in Sabangau District, Palangka Raya City. This type of research is descriptive quantitative research by conducting interviews and giving questionnaires to 95 respondents of Micro, Small and Medium Enterprises (MSMEs) in Sabangau District, Palangka Raya City using multiple linear regression analysis tools. The results of the analysis show that partially capital production costs and length of business have a significant effect on income. Simultaneously, capital, production costs and length of business have a significant effect on income